(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
When cotton fibers are cleaned, there is a very high chance that they will come into contact with one another in a single particle. When it comes to technical activities, a group of cotton fibers made up of several fibers may interact with a machine’s working parts more frequently than a single cotton filament. It should be noted that the continuous media theory must be applied in order to describe the movement of cotton fiber during cleaning, pipe movement, removal from the saw teeth of a spinning gin machine with the aid of an air stream, and removal from the machine after the air has been removed.